Evaluation of Structural Shrinkage on Freeze-Dried Fruits by Image Analysis: Effect of Relative Humidity and Heat Treatment - Agudelo Laverde, Lina Marcela (2014)
Stability of many dehydrated systems is related to the formation of a glass during drying. Highly porous materials, such as those prepared by freeze-drying are susceptible to shrinkage post-drying when stored at not optimal conditions. The aim of this study was to evaluate the occurrence of structural shrinkage on freeze-dried fruits through image analysis in relation to relative humidity (RH) and heat treatment. Freeze-dried fruits were humidified between 11 and 84 % RH at 25 °C for 14 days, and then stored at 45 °C. Sugar and water content, thermal transitions, and volume changes were determined. The shrinkage degree of fresh, lyophilized, humidified, and heat-treated samples was assessed by image analysis. The freeze-drying process did not produce important changes on fruits volume. At low RH values (11–22 % RH), the reduction of the cylinders volume was lower than 15 %. The maximum shrinkage values at each RH were attained in the initial period of humidification (first and second days), and then shrinkage rate decreased markedly, reaching a nearly constant value. The shrinkage degree increased with the increase in RH, reaching values up to 60 % volume reduction. During heat treatment, the volume reduction was less than 10 %. The shrinkage degree was limited by the structural characteristics of the fruits. The structural changes were strongly influenced by variables such as water content, glass transition temperatures, and storage time. In this work, the degree of shrinkage could be followed by image analysis and the use of a mechanical modeling software.